Prediksi Jumlah Pengunjung Semarang Zoo dengan Metode Fuzzy Time Series - Marzuqi, Muhammad; Tafrikan, Mohammad; Maslihah, Siti (Universitas Islam Madura, 2022)
Forecasting is a very important element in making decisions to deal with uncertain situations. The purpose of this study is to determine the results of forecasting using the fuzzy time series method so that it can be used as a basis for the Semarang Zoo management in planning development. This study uses secondary data from PT Taman Satwa Semarang. Data on the number of visitors to the Semarang Zoo from January 2017 to December 2021. The steps in this research are formulating problems, collecting data, analyzing data, and drawing conclusions. The calculation technique is carried out in two ways, namely manually and using the RStudio application. The result of this research is that the prediction results for January 2022 are 34,640 for manual calculations and 34,430 for calculations using the Rstudio application. While the MAPE test results obtained 14.15% for manual calculations and 15.082% for calculations using the Rstudio application. . Keywords: forecasting, fuzzy time series, number of visitors